نظرة المجتمع إلى التقنیات الحدیثة في تنظیم الأسرة (دراسة نظریة في علم الاجتماع الطبي) (Journal of the College of Education for Women, 2019)
Human use means of birth control in multiple ways including (Isolatewomen) and (breast-feeding) and (with drawl) and was used on a small scale forreligious social and economic reasons, but after the industrial Revolution and theincrease in migration from the country side to the city and the over cowing ofpopulation and the limited income and a women going out to work out side thehome and poor relations of the kinship and the weakness of religious morals andthe rule of the individualism and the complexity of life and the Multiplicity ofneeds and goals and openness to western culture and the application of love andspread the principle of democracy and freedom and deviant use of the media, allthis has helped in the popularity of the use of modern family planning methodswhich are limited to the following :1. Contraceptives by mouth through medicines and pharmaceuticals .2. Intra-uterine devices for contraception made of special plastic or copper.3. Contraception by injection of medical preparation .4. New methods of fertility regulation and improved throw anew research andstudies that will help in devising means more receptive and the safety andeffectiveness and far from the expected collateral damage .